2012
DOI: 10.1002/pola.26458
|View full text |Cite
|
Sign up to set email alerts
|

Linear and star‐shaped POSS hybrid materials containing crystalline isotactic polystyrene chains

Abstract: New crystalline nanostructured inorganic–organic hybrid materials containing isotactic polystyrene (iPS) are prepared by means of hydrosilylation coupling of vinyl‐terminated iPS with octakis(dimethylsilyloxy)silsesquioxane (Q8M8H). The number average molar mass of the iPS chains varies between 2000 and 6000 g mol−1. As a function of the iPS/Q8M8H ratio, using excess reagent, the formation of linear or star‐shaped hybrid architectures is achieved. Via fractionation, it is possible to isolate well‐defined linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Hence, we presume that the growing crystalline domains in combination with the POSS centers connecting multiple iPS chains give rise to an environment confining the noncrystalline chains in a similar fashion. The observation that POSS–iPS with shorter polymer chains do not crystallize at all indicates that the crystallites grow only in sufficient distance from the POSS centers because of steric hindrance in their vicinity. Similar findings were reported for other polymers. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we presume that the growing crystalline domains in combination with the POSS centers connecting multiple iPS chains give rise to an environment confining the noncrystalline chains in a similar fashion. The observation that POSS–iPS with shorter polymer chains do not crystallize at all indicates that the crystallites grow only in sufficient distance from the POSS centers because of steric hindrance in their vicinity. Similar findings were reported for other polymers. …”
Section: Resultsmentioning
confidence: 99%
“…Dielectric spectroscopy measurements reveal an unusual alteration of the segmental dynamics of a star-shaped polymer upon crystallization. The molecule consisting of a POSS kernel with 6–8 iPS chains attached to its edges exhibits an increase of the mean relaxation rate of the segments compared to the purely amorphous state. A detailed analysis of the extracted relaxation time distribution unravels three amorphous moieties which differ in their dynamics: (i) a rigid amorphous fraction, (ii) a mobile amorphous fraction (as found in the purely amorphous sample), and (iii) a confined amorphous fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Möller et al and later De Carlo et al reported the synthesis of highly isotactic PS and substituted styrenes in the presence of the catalyst dichloro­[1,4-dithiabutanedyi-2,2′-bis­(4,6-di- tert -butyl-phenoxy)]­titanium, together with a great number of studies on its application for the isospecific coordination polymerization of styrene including functional iPS. Recently, Nakata et al . reported the development of [OSSO]-type bis­(phenolate) catalysts based on a trans -1,2-cyclooctanediyl platform associated with several early transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…This makes POSS molecules excellent platforms and blocks for nanotechnology applications and architecture of novel organic-inorganic hybrid nanocomposites. [4][5][6] More importantly, POSS molecules offer a unique opportunity for preparing organic-inorganic molecular hybrids with the inorganic structural units covalently incorporated and truly molecularly dispersed into resultant hybrids, which effectively overcomes the aggregation effect that occurs in common hybrid composites based on physical mixtures. [7][8][9][10][11] Thus, the POSS molecules with unique structures provide many possibilities and opportunities to tailor the properties of materials.…”
Section: Introductionmentioning
confidence: 99%